Determination of Exercise Attitudes of Pregnant Women - Acari, Sevgi; Sivrikaya, Omer (Asian Journal of Education and Training, 2022)
It is known that pregnancy is essential in the contribution of exercise to human health and the formation of healthy societies. Phenomenology design, one of the qualitative research techniques, was used in the research. The attitudes of pregnant women towards exercise before and during pregnancy and the factors affecting these attitudes were examined. The research group comprises 10 pregnant women, who are university graduates and work as professionals, who voluntarily participated in the research while living in Düzce. It is assumed that university graduates and professional pregnant women are the most qualified part of society in terms of health awareness and sports habits. A semi-structured interview form was used to collect data. Face-to-face interviews were conducted with pregnant women from different professions and at different stages of their pregnancy. NVIVO 11 statistical program was used in the analysis of the data. Although the participants thought that it was beneficial for their health, it was determined that they had various fears. Due to these fears and the fact that specialist doctors do not recommend exercise, even pregnant women who did not have any problems during their pregnancy avoided exercising. It was observed that the exercise attitudes of the participants before and during pregnancy differed.